2013
DOI: 10.1002/star.201200244
|View full text |Cite
|
Sign up to set email alerts
|

Maize and teff starches modified with stearic acid as potential fat replacer in low calorie mayonnaise‐type emulsions

Abstract: Fat replacers have been developed to produce low-calorie foods due to the association of fat-rich diet to lifestyle diseases. Teff (an underutilized and under-researched cereal), and maize starch pastes modified with stearic acid could be used as fat replacers because of their reduced gelling ability and higher viscosity. The effect of teff and maize starch pastes modified with stearic acid on the rheological properties, microstructure, freeze-thaw and high temperature stability of lowcalorie mayonnaise type e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
(26 reference statements)
5
29
0
Order By: Relevance
“…Table 1 shows the statistical analysis reported that the general trend indicated a more number of oil droplets with smaller mean area as the oil was gradually replaced by the extruded flour. These observations are consistent with the findings of Mun et al (2009) andTeklehaimanot et al (2013) for mayonnaises in which the oil was replaced by enzymatically and chemically modified starches, respectively. Regarding the amount of water of the paste, the mean area of the droplets did not show significant differences for any of the levels of oil substitution.…”
Section: Microstructuresupporting
confidence: 91%
See 3 more Smart Citations
“…Table 1 shows the statistical analysis reported that the general trend indicated a more number of oil droplets with smaller mean area as the oil was gradually replaced by the extruded flour. These observations are consistent with the findings of Mun et al (2009) andTeklehaimanot et al (2013) for mayonnaises in which the oil was replaced by enzymatically and chemically modified starches, respectively. Regarding the amount of water of the paste, the mean area of the droplets did not show significant differences for any of the levels of oil substitution.…”
Section: Microstructuresupporting
confidence: 91%
“…An increase in stability was only observed when the water content was increased between 1:3 and 1:4 ratios of the 30% and 50% level of substitution. Teklehaimanot et al (2013) also found an increase of freeze stability when the fat was replaced by a chemically modified starch paste. This phenomenon could be attributed to the hydrophilic nature of the paste, which may stabilise water during crystallisation and maintain separated the oil droplets, protecting against possible coalescence.…”
Section: Emulsion Stability and Freeze-thaw Stabilitymentioning
confidence: 86%
See 2 more Smart Citations
“…Teff starch contains 2–6 mm granules, with a little dissimilar properties in comparison with other tropical starches, and has been suggested as a good fat mimetic. Teklehaimanot, Duodu, and Emmambux () investigated the impact of maize and teff starch pastes amended by stearic acid on the microstructure and rheological characteristics of low‐fat mayonnaise. They reported that both of modified and unmodified maize and teff starches could produce low‐fat mayonnaises at 50% replacement for oil.…”
Section: Conditions Used To Produce Healthy and Functional Mayonnaisementioning
confidence: 99%